Strategi Pemasaran Produk Kacang Mete pada UD. Mete Mubarok Lombe Kota Kendari - Damin, Desri Asfrianti; Mukhtar, Mukhtar; Gafaruddin, Abdul (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
The purpose of this research is to investigate the strength, weakness, opportunity, and threat of the ripe mete product marketing at UD. Mete Mubaroq Lombe and investigate the strategy of ripe mete product marketing at UD. Mete Mubaroq Lombe. Technique of data analysis that used is descriptive analysis and SWOT analysis. Base on the research finding at UD. Mete Mubaroq Lombe can be known that became the strength is the quality of the product which has delicious taste and more bigger also it has more high price because its quality serves delicious taste, the strategic location means it is reachable. The weakness is the finance note still simple because less of computer technology, less of promotion activity the industry only uses a notice in the street and billboard in front of the industry, and in a certain month the price of the basic material is increasing because the harvest is not maximal caused unpredictable rain. The opportunity with the rise of innovation and creation this business has big opportunity to dominate the market, there are many consumers in other location because cashew is a kind of good which is traded nationally and internationally, and the request is increasing in the certain season for example in the Eid Mubaroq and in certain events. The threat is harvest fail that make limitation of the supply of material means the rain is too rise so the harvest is less or nothing, and the rise of the same business because cashew is one of Kendari gift so people have willing to open its business. The marketing strategy used at UD. Mete Mubaroq Lombe is aggression business strategies means the industry is in prima condition and constant so it is very probably to do business improvement and gain advance maximally.